2010
DOI: 10.1073/pnas.0911972107
|View full text |Cite
|
Sign up to set email alerts
|

Optimal reward harvesting in complex perceptual environments

Abstract: The ability to choose rapidly among multiple targets embedded in a complex perceptual environment is key to survival. Targets may differ in their reward value as well as in their low-level perceptual properties (e.g., visual saliency). Previous studies investigated separately the impact of either value or saliency on choice; thus, it is not known how the brain combines these two variables during decision making. We addressed this question with three experiments in which human subjects attempted to maximize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
151
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(167 citation statements)
references
References 35 publications
16
151
0
Order By: Relevance
“…Several recent studies have shown that the voluntary deployment of attention is influenced by reward (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). In contrast to the ample evidence that voluntary deployment of attention to taskrelevant stimuli is affected by reward, the evidence for an influence of the value assigned to stimuli through reward learning on involuntary attentional capture is negative or equivocal (10)(11)(12)26).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Several recent studies have shown that the voluntary deployment of attention is influenced by reward (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). In contrast to the ample evidence that voluntary deployment of attention to taskrelevant stimuli is affected by reward, the evidence for an influence of the value assigned to stimuli through reward learning on involuntary attentional capture is negative or equivocal (10)(11)(12)26).…”
Section: Discussionmentioning
confidence: 88%
“…Voluntary attention to stimuli that predict reward is an effective mechanism for efficiently selecting valuable stimuli (9). Many studies have shown that reward facilitates voluntary attention to task-relevant stimuli, and that reward-based strategies and priorities strongly influence attentional performance (10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…One possibility is that our visual search task is broadly insensitive not just to spatial reward magnitude learning but to many forms of magnitude learning. As mentioned in the introduction, several researchers have reported robust prioritization of features that are associated with greater monetary reward (e.g., Anderson, et al, 2011;Kiss et al, 2009;Navalpakkam et al, 2010). In Experiment 2, we test whether the visual search task used in Experiment 1 produces learning of feature magnitude.…”
Section: Methodsmentioning
confidence: 99%
“…Just one study has reported that individuals learn to bias spatial attention to locations containing more valuable targets . Note that, overall, the number of studies of attention and reward have surged in recent years, most of which have shown robust prioritization of rewarded nonspatial features (e.g., Anderson, Laurent, & Yantis, 2011;Della Libera & Chelazzi, 2006;Hickey, Chelazzi, & Theeuwes, 2010;Kiss, Driver, & Eimer, 2009;Navalpakkam, Koch, Rangel, & Perona, 2010). Given the traditionally strong focus of attention research on spatial attention (Bisley & Goldberg, 2010;Fecteau & Munoz, 2006), one might expect more published studies demonstrating learning of spatial reward magnitude.…”
mentioning
confidence: 99%
“…Indeed, it is likely that value-driven and physical bottom-up processes operate independently. When visual salience and value information vary independently within a complex perceptual context, both variables combine to influence performance in a way that maximises reward (Navalpakkam, Koch, Rangel, & Perona, 2010).…”
Section: Learning To Attend: Effects Of Predictiveness On Perception mentioning
confidence: 99%